ROUTINES CONFLICT COMMOGNITIVE IN STUDENTS' WORK RESULTS ON THE MATERIAL OF INDEFINITE FORM LIMITS - Emanuel, Endrayana Putut Laksminto; Anam, Fatkul; Iventri, Kuirinus; El Walida, Sikky (Universitas Sembilanbelas November Kolaka, 2025)
This research aims to describe cognitive conflicts that occur in first year students when solving indefinite form limit problems. This research is qualitative research with the researcher as the main instrument. Research method with stages of preparation, data collection, transcript and analysis. A total of 8 students from private universities were given mathematics problem sheets, containing limit questions of indefinite form consisting of one number and worked on for 30 minutes. Two students were selected as research subjects based on indicators of conflict in the components of routines and were interviewed in a semi-structured and in-depth manner to explore further information about the causes of conflict. The results of the research showed that the research subjects were able to solve the questions given but there were errors that triggered conflict, both ritualized and exploratory. . Ritualized due to weak understanding of material previously received in high school. Exploratory, which is a new or different method because it is not well understood, can cause cognitive conflict. Good mastery and understanding of the material can reduce the occurrence of cognitive conflicts in students' minds.